The Gorlin-Goltz Syndrome: diagnosis of a case associated with heart disease and type 2 diabetes mellitus - João Paulo Nunes Drumond; Bruna Bianca Allegro; Wilson Roberto Sendyk; Fabiana Martins e Martins de Oliveira (Revista Brasileira de Cirurgia Plástica)
The Gorlin-Goltz syndrome (GGS) is a hereditary, autosomal dominant condition, with high penetrance and variable expressivity, resulting from mutations in the genes PTCH1, PTCH2, or SUFU. The diagnosis is based on the presence of 2 major criteria or a major criterion associated with 2 minor criteria, including multiple basal cell carcinomas, keratocystic odontogenic tumor (KOT), and bifid rib. Other endocrine, neurological, ophthalmologic, genital, respiratory, and cardiovascular alterations are found in the literature, but with variable manifestations. This study reports the case of a patient diagnosed with GGS associated with diastolic congestive heart failure and type 2 diabetes mellitus, who underwent multiple treatments for components of the syndrome. More recently, the patient underwent decompression followed by cystic enucleation of two KOTs in the jaw, oral rehabilitation with removable prosthodontics, cardiological evaluation, and attempted clinical control of endocrine and cardiac problems.